A polyhistor landscape architect - Körmendy, Imre (4D Journal of Landscape Architecture and Garden Art, 2021)
It is a great venture to present a man and his life, especially when the man has lived for almost a century and his work is equally enormous. The nine authors, and especially the three editors, have undertaken this almost impossible task, and Mihály Mőcsényi's life reveals a century of Hungarian history and the fate of our country. An EasternCentral European fate in every inch. Studying his writings, a man appears to the reader; not "The PROF", as I have heard from many in the last decade, and which frightened me, because he has become a concept from a person with this designation, with the definite article, with the capital letter (orally, with the emphasis).
Keywords: Mőcsényi